EXPRESSION OF ARABIC PLURAL IN CERTAIN NOUNS IN NAVOYI'S EPIC "SADDI ISKANDARI" (Scientific journal of the Fergana State University, 2025)
Annotation: This article talks about the plural form of some nouns, Arabic plural suffixes, broken plural form in Alisher Navoi's epic "Saddi Iskandarii". The morphological characteristics of some words in the work, their lexical meanings, the fact that they are based on explanations in Persian-Tajik dictionaries, and the lexical meanings of Persian words in the annotated dictionary of Navoi's works are presented. The main goal of the article is to determine the nouns formed as a result of the addition of Arabic plural suffixes, and the presence of Arabic broken plural in some of them. The lexical and semantic features of the Persian words mentioned in the article are explained.